The design of "TeamBirth": A care process to improve communication and teamwork during labor. Issue 4 (9th July 2021) - Aggarwal, Reena; Plough, Avery; Henrich, Natalie; Galvin, Grace; Rucker, Amber; Barnes, Chris; Berry, William; Golen, Toni; Shah, Neel T.
Abstract: Background: Despite evidence that communication and teamwork are critical to patient safety, few care processes have been intentionally designed for this purpose in labor and delivery. The purpose of this project was to design an intrapartum care process that aims to improve communication and teamwork between clinicians and patients. Methods: We followed the "Double‐Diamond" design method with four sequential steps: Discover, Define, Develop, and Deliver. In Discover, we searched professional guidelines and peer‐reviewed literature to delineate the challenges to quality of intrapartum care and to uncover options for solutions. In Define, we convened an interdisciplinary group of experts to focus the problem scope and prioritize solution features. In Develop, we created initial prototype solutions. In Deliver, we engaged clinicians and patients in rapid cycle testing to iteratively produce a care process called "TeamBirth" that aims to improve team communication. Results: We designed TeamBirth, an intrapartum care process composed of brief team meetings ("huddles") between clinicians and patients. Huddles are navigated by a shared planning board placed in the labor and delivery room in view of the patient and their care team. The board promotes transparent and reliable communication and contains four areas to be acknowledged or discussed: (a) the names of the team members, starting with the patient; (b) the patient's preferences; (c) the care plan for the patient, baby, and labor progress; and (d) when the next team huddle is anticipated. Discussion: We identified an opportunity to improve the safety and dignity of childbirth care through an intrapartum care process that promotes reliable and structured communication and teamwork. Future work should evaluate the acceptability and feasibility of implementation and potential impact on safety and experience of care.